2021
DOI: 10.1177/20552076211002103
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of collecting speech samples from the elderly via the telephone

Abstract: Objective There is a critical need to develop rapid, inexpensive and easily accessible screening tools for mild cognitive impairment (MCI) and Alzheimer’s disease (AD). We report on the efficacy of collecting speech via the telephone to subsequently develop sensitive metrics that may be used as potential biomarkers by leveraging natural language processing methods. Methods Ninety-one older individuals who were cognitively unimpaired or diagnosed with MCI or AD participated from home in an audio-recorded teleph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Participants comprised 91 older individuals who were cognitively unimpaired ( n = 29, mean age = 72.48 [SD = 1.47], mean years of education = 18.00 [SD = 0.37], 41% female) or diagnosed with aMCI ( n = 32, mean age = 74.03 [SD = 1.01], mean years of education = 17.34 [SD = 0.30], 41% female) or mild AD ( n = 30, mean age = 74.93 [SD = 1.40], mean years of education = 16.68 [SD = 0.43], 52% female) 9,26 . The group demographics did not differ significantly ( p ‐values > 0.01).…”
Section: Methodsmentioning
confidence: 99%
“…Participants comprised 91 older individuals who were cognitively unimpaired ( n = 29, mean age = 72.48 [SD = 1.47], mean years of education = 18.00 [SD = 0.37], 41% female) or diagnosed with aMCI ( n = 32, mean age = 74.03 [SD = 1.01], mean years of education = 17.34 [SD = 0.30], 41% female) or mild AD ( n = 30, mean age = 74.93 [SD = 1.40], mean years of education = 16.68 [SD = 0.43], 52% female) 9,26 . The group demographics did not differ significantly ( p ‐values > 0.01).…”
Section: Methodsmentioning
confidence: 99%
“…Voice is a proven source of medical information, can be easily recorded on a large scale through smart devices [ 25 ], and can be easily used to build personalized corpora [ 26 ]. Studies have shown great results in the early diagnosis of neurological disorders such as Parkinson disease [ 27 , 28 ], Alzheimer disease [ 29 ], and mild cognitive impairment [ 30 , 31 ], since they directly alter the voice, but also in nonneurological conditions such as cardiometabolic [ 32 ] and pulmonary [ 33 ] diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Two different datasets were examined to illustrate the contrast between high- and low-quality audio recordings: (1) Telephone data - from a study assessing the cognitive state of older participants ( Diaz-Asper et al, 2021 ). Participants ( N = 91) were community dwelling, older English speakers (mean age = 73.7 ± 6.9 years of age) who had been called at home (on landlines, cellphones and speaker phones) and spoke for several minutes about past memorable experiences or hobbies.…”
Section: Methodsmentioning
confidence: 99%